LEGAL REGULATION OF HIGHER EDUCATION RESULTS AND EDTECH TOOLS IN THE CONTEXT OF RESTRICTIONS ON THE SPREAD OF COVID-19 IN LATVIA AND RUSSIA - Andreanova, Inna; Rozhkova, Anna; Bulgakova, Ilona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The use of EdTech tools to achieve higher education results in the context of restrictions on the spread of Covid-19 transforms both the process of higher education and reflects the need to make corrections in the formulation of the results of traditional higher education in social and humanitarian areas of training. The article proposes an analysis of the regulation of the results of higher education and the use of EdTech-tools in accordance with the current standards. Generalization of the competence of subjects of educational activity in the formation of individual educational results allows segmenting into traditional and alternative carriers of educational products. A roadmap for achieving compliance of quality criteria of EdTech tools for improving the results of higher education is proposed.